The online learning idea book. - Shank, Patti, 1954- (Pfeiffer essential resources for training and HR professionals., 2011)
Many books recommend teaching and learning strategies based on current learning research and theory. However, few books offer illustrative examples of how to take these strategies and put them into action in the real world. The Online Learning Idea Book is filled with concrete examples of people who make learning more inspiring and engaging every day, in all kinds of settings, all over the world. In this second volume of The Online Learning Idea Book you will find brand new and valuable ideas that you can adopt or adapt in your own instructional materials, to make them more dyn.